Long-term outcomes of ranibizumab vs. aflibercept for neovascular age-related macular degeneration and polypoidal choroidal vasculopathy - Jin, Ki Won (Sci Rep, 2021)
To evaluate the long-term outcomes of ranibizumab (RBZ) vs. aflibercept (AFL) in treatment-naïve eyes with typical neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV). This multicenter, retrospective, matched-cohort analysis was conducted on data  up to 4 years of follow-ups. The primary outcome was the visual acuity (VA) change from baseline. The secondary outcomes included the number of injections, proportion of eyes without a yearly injection, and the number of eyes with treatment switching. Subgroup analyses were performed for typical nAMD and PCV. Typical nAMD was defined as nAMD other than PCV. We included VA-matched 215 eyes of 209 patients (131 and 84 eyes with RBZ and AFL, respectively). The crude mean VA changes from baseline were + 6.7 vs. + 2.6, + 2.1 vs. − 0.4, − 1.3 vs. − 1.8, and − 2.2 vs. − 5.0 letters in the RBZ and AFL groups, at 1, 2, 3, and 4 years, respectively (p > 0.05). The adjusted predicted VA by linear mixed model, proportion of eyes stratified by VA, and the survival curve for significant vision loss were comparable during the 4-year follow-up (p > 0.05). The mean number of injections were similar between the RBZ and AFL groups (2.9 vs. 3.0, respectively, p = 0.692). The subgroup analysis for typical nAMD and PCV showed similar results between the groups. The visual outcomes did not differ between RBZ and AFL during 4 years with comparable numbers of injections. Our study reflects the long-term, real-world clinical practice and treatment pattern of two treatments for typical nAMD and PCV.